Becoming authoritarian for the greater good? Authoritarian attitudes in context of the societal crises of COVID-19 and climate change - Hirsch, Magdalena (Frontiers in Political Science, 2022)
Authoritarianism is widely conceived as destructive phenomenon that threatens liberal societies. However, some scholars suggest that authoritarianism is beneficial both for individuals’ sense of control and agency and goal attainment within groups. In line with this reasoning, collective problems, such as the COVID-19 crisis and climate change, may go hand in hand with increased levels of authoritarianism. While individuals may generally support abstract values of individual freedom and democratic rule, societal threat may require individuals to weigh liberal values against needs for collective unity and action. Thus, I expect a gap between abstract authoritarianism and crisis-related authoritarianism that is targeted at dealing with a specific societal threat. Following the idea that authoritarianism serves as an antiliberal means for achieving collective goals, discrepancies between abstract and crisis-related authoritarianism hinge on the rejection of the means being outweighed by the perceived importance of the goal. While authoritarian disposition captures general tendencies to accept the means, trust in science serves as a proxy for the perceived importance of COVID-19 and climate change mitigation. The increase in support of crisis-related authoritarianism relative to abstract authoritarianism should be particularly pronounced among individuals who are not predisposed to authoritarianism and who trust in science. Findings from a cross-national, representative survey experiment in Germany (N = 1480) and Spain (N = 1511) support this reasoning. Participants answered four items covering authoritarian submission and aggression either on an abstract level (control group), or applied to the COVID-19 crisis or the climate change crisis. Participants were more supportive of authoritarian ideas targeted at a specific collective problem as compared to abstract authoritarian ideas. Furthermore, the differences in authoritarianism between the control group and the two societal crisis conditions decreased with authoritarian disposition and increased with trust in science. Exploratory analyses suggest that the main differences across experimental conditions are driven by authoritarian submission while the interaction effects are rather driven by authoritarian aggression. The study underlines the role of authoritarian ideas for collective goal attainment that exists above and beyond stable personal dispositions. As such, it sheds light on the conditions under which citizens conceive authoritarianism as justifiable.